2007
DOI: 10.1088/0957-0233/19/1/015205
|View full text |Cite
|
Sign up to set email alerts
|

A novel eddy current angle sensor for electrohydraulic rotary valves

Abstract: We present an eddy current angle sensor for high-pressure electrohydraulic rotary valves. An oblique ring-shaped sensing coil and a symmetric semi-cylindrical rotor are utilized, making the coil impedance and the output voltage proportional to the angular displacements. Analysis based on an electrical equivalent circuit and the finite-element method is provided, and good agreement is obtained between the simulated and measured results. Extensive experiments have shown that the sensor has a linear working range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…[61], the large range (30 degrees) is obtained by a special mechanical construction: the rotating part has a semi-cylindrical shape, turning in a coil that makes an angle with the axis. [61], the large range (30 degrees) is obtained by a special mechanical construction: the rotating part has a semi-cylindrical shape, turning in a coil that makes an angle with the axis.…”
Section: Angular Displacementmentioning
confidence: 99%
“…[61], the large range (30 degrees) is obtained by a special mechanical construction: the rotating part has a semi-cylindrical shape, turning in a coil that makes an angle with the axis. [61], the large range (30 degrees) is obtained by a special mechanical construction: the rotating part has a semi-cylindrical shape, turning in a coil that makes an angle with the axis.…”
Section: Angular Displacementmentioning
confidence: 99%
“…Angular rate sensing uses a physical phenomenon intrinsically related to the rate of angular rotation. For example, in vibratory gyroscopes, Coriolis forces depend on angular velocity and therefore a measurement of motion due to 3 Both of these authors contributed equally to the work in this paper.…”
Section: Motivationmentioning
confidence: 99%
“…Unlike relative angle sensors, absolute angle sensors attempt to measure the inertial angle of a rotating frame directly [3,4]. While absolute angle sensors are under development and are a topic of research, a working prototype of an absolute angle sensor has not yet been demonstrated.…”
Section: Motivationmentioning
confidence: 99%
“…Inductive angle sensors provide a compact structure and a high degree of insensitivity to production and installation tolerances, but the weak linear relationships between position and output signal (near the zero crossings) often lead to significant nonlinearity errors for calculating the angular displacement [ 11 , 12 ]. In the inductive position sensor field, the nonlinearity error is around one percent [ 7 , 13 , 14 ]. To reduce the nonlinearity error, the sensor structure needs to be optimized.…”
Section: Introductionmentioning
confidence: 99%